Transformational Leadership In Maritime Cadet Development: An Integrative Review Of Motivation, Safety Culture And Professional Identity Formation - Inriani Inriani (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
The maritime industry increasingly requires highly competent professionals capable of operating in technologically advanced, dynamic, and safety-critical environments. As future maritime officers, marine cadets must develop not only technical competencies but also leadership capabilities, safety awareness, professional commitment, and psychological resilience. Leadership within Maritime Education and Training (MET) institutions therefore plays a crucial role in shaping cadet development and readiness for professional practice. This study aims to examine the influence of transformational leadership on maritime cadet development, particularly regarding motivation, learning engagement, safety culture internalization, and professional identity formation. An Integrative Literature Review (ILR) methodology was employed following established review procedures and PRISMA guidelines. Relevant studies were collected from Scopus, Web of Science, ScienceDirect, SpringerLink, Emerald Insight, and Taylor & Francis databases, covering publications from 2000 to 2025. A total of 67 studies met the inclusion criteria and were analyzed through thematic synthesis. The findings indicate that transformational leadership contributes positively to cadet development through four key dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. These leadership dimensions enhance self-efficacy, intrinsic motivation, learning engagement, professional identity, safety awareness, and psychological resilience, which subsequently influence behavioral outcomes such as persistence, academic performance, teamwork, problem-solving ability, and safety behavior. The review further identifies organizational culture, instructor credibility, psychological safety, and training design as important moderating factors affecting leadership effectiveness. The study proposes a conceptual model linking transformational leadership to maritime professional readiness and offers practical implications for leadership development initiatives within maritime academies. The findings contribute to leadership theory and maritime education literature by providing a comprehensive understanding of leadership-driven cadet development processes.